Kata Serapan Bahasa Arab Dalam Bahasa Suku Aneuk Jamee Di Aceh: Loanwords from the Arabic language in the Anyok Jami tribe's language in the Aceh region. - Ibrahim, Malik; Sofyan, Zulkhairi; Suhemi, Emi (Universitas Darussalam Gontor, 2025)
Abstract (English) This research deals with words borrowed from Arabic language in the language of the Aneuk Jamee tribe in Aceh province. Research uses the analytical descriptive approach to analyse this phenomenon. The main goal of the search is to identify words absorbed from Arabic and understand their impact on Aneuk Jamee's language. The aliases are analyzed based on a series of Arabic letters. The aliases are found in 20 different letters of the alphabet. The results of the study show that there are several words in Aneuk Jamee language that are heavily influenced in Arabic and cover different areas of daily life such as religion, education and literature, showing the influence of Arabic language in various aspects of cultural and social life. The results of the research show that there are a number of words in Aneuk Jami's language that are highly influenced by Arabic. These results provide a clearer picture of the process of borrowing words between these two languages, as well as their implications for linguistic identity. from the Aneuk Jamee tribe in Aceh. Keywords: borrowed words, Arabic language, Aneuk Jamee language Ø§Ù„Ù…Ù„Ø®Øµ ÙŠØªÙ†Ø§ÙˆÙ„ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…Ù‚ØªØ±Ø¶Ø© Ù…Ù† Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù„ØºØ© Ù‚Ø¨ÙŠÙ„Ø© Ø£Ù†ÙˆÙƒ Ø¬Ø§Ù…ÙŠ ÙÙŠ Ù…Ù‚Ø§Ø·Ø¹Ø© Ø£ØªØ´ÙŠÙ‡. ÙˆÙŠØ³ØªØ®Ø¯Ù… Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…Ù†Ù‡Ø¬ Ø§Ù„ÙˆØµÙÙŠ Ø§Ù„ØªØÙ„ÙŠÙ„ÙŠ Ù„ØªØÙ„ÙŠÙ„ Ù‡Ø°Ù‡ Ø§Ù„Ø¸Ø§Ù‡Ø±Ø©. Ø§Ù„Ù‡Ø¯Ù Ø§Ù„Ø±Ø¦ÙŠØ³ÙŠ Ù…Ù† Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø§Ù„ØªØ¹Ø±Ù Ø¹Ù„Ù‰ Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…Ù…ØªØµØ© Ù…Ù† Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆÙÙ‡Ù… ØªØ£Ø«ÙŠØ±Ù‡Ø§ Ø¹Ù„Ù‰ Ù„ØºØ© Ø£Ù†ÙŠÙˆÙƒ Ø¬Ø§Ù…ÙŠ. ÙŠØªÙ… ØªØÙ„ÙŠÙ„ Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…Ø³ØªØ¹Ø§Ø±Ø© Ø¨Ù†Ø§Ø¡Ù‹ Ø¹Ù„Ù‰ Ø³Ù„Ø³Ù„Ø© Ù…Ù† Ø§Ù„ØØ±ÙˆÙ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ ÙˆØªÙˆØ¬Ø¯ Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…Ø³ØªØ¹Ø§Ø±Ø© ÙÙŠ 20 ØØ±ÙÙ‹Ø§ Ù…Ø®ØªÙ„ÙÙ‹Ø§ Ù…Ù† Ø§Ù„ØØ±ÙˆÙ Ø£Ùˆ Ø§Ù„Ø£ØµÙˆØ§ØªØŒ ÙˆØªØ¸Ù‡Ø± Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¯Ø±Ø§Ø³Ø© Ø£Ù† Ù‡Ù†Ø§Ùƒ Ø¹Ø¯Ø© ÙƒÙ„Ù…Ø§Øª ÙÙŠ Ù„ØºØ© Ø£Ù†ÙˆÙƒ Ø¬Ø§Ù…ÙŠ Ù…ØªØ£Ø«Ø±Ø© Ø¨Ø´Ø¯Ø© Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØªØºØ·ÙŠ Ù…Ø¬Ø§Ù„Ø§Øª Ù…Ø®ØªÙ„ÙØ© Ø§Ù„ØÙŠØ§Ø© Ø§Ù„ÙŠÙˆÙ…ÙŠØ© ÙƒØ§Ù„Ø¯ÙŠÙ† ÙˆØ§Ù„ØªØ¹Ù„ÙŠÙ… ÙˆØ§Ù„Ø£Ø¯Ø¨ØŒ Ù…Ù…Ø§ ÙŠØ¸Ù‡Ø± ØªØ£Ø«ÙŠØ± Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ Ù…Ø®ØªÙ„Ù Ø¬ÙˆØ§Ù†Ø¨ Ø§Ù„ØÙŠØ§Ø© Ø§Ù„Ø«Ù‚Ø§ÙÙŠØ© ÙˆØ§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ©. Â ÙˆØªØ¸Ù‡Ø± Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¨ØØ« Ø£Ù† Ù‡Ù†Ø§Ùƒ Ø¹Ø¯Ø¯Ø§ Ù…Ù† Ø§Ù„ÙƒÙ„Ù…Ø§Øª ÙÙŠ Ù„ØºØ© Ø£Ù†ÙˆÙƒ Ø¬Ø§Ù…ÙŠ Ù…ØªØ£Ø«Ø±Ø© Ø¨Ø´ÙƒÙ„ ÙƒØ¨ÙŠØ± Ø¨Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. ÙˆØªÙ‚Ø¯Ù… Ù‡Ø°Ù‡ Ø§Ù„Ù†ØªØ§Ø¦Ø¬ ØµÙˆØ±Ø© Ø£ÙˆØ¶Ø Ù„Ø¹Ù…Ù„ÙŠØ© Ø§Ø³ØªØ¹Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø¨ÙŠÙ† Ù‡Ø§ØªÙŠÙ† Ø§Ù„Ù„ØºØªÙŠÙ†ØŒ ÙØ¶Ù„Ø§ Ø¹Ù† Ø§Ù†Ø¹ÙƒØ§Ø³Ø§ØªÙ‡Ø§ Ø¹Ù„Ù‰ Ø§Ù„Ù‡ÙˆÙŠØ© Ø§Ù„Ù„ØºÙˆÙŠØ©. Ù…Ù† Ù‚Ø¨ÙŠÙ„Ø© Ø£Ù†ÙˆÙƒ Ø¬Ø§Ù…ÙŠ ÙÙŠ Ø£ØªØ´ÙŠÙ‡.